An analysis of the most recent scientific evidence: is ketamine the solution for treating patients with depression? - Nuss, Ana Carolina (2025)
Depression is one of the main causes of disability worldwide and a significant portion of patients do not respond adequately to available treatments, triggering the need for new pharmacological options. Originally developed as an anesthetic and known for abuse potential, ketamine has recently been reevaluated as a medication for depression, especially in resistant cases. The objective of this research is to analyze the use of ketamine as a therapeutic alternative for the treatment of resistant depression. The methodology used was an integrative literature review, with analysis of clinical studies published in the last 5 years, through the combination of the terms “ketamine” and “antidepressant” in PubMed, ScienceDirect, Google Scholar and LILACS databases. The search strategy resulted in 322 articles and, of these, 13 were used in the research. The data showed that ketamine provides a rapid reduction in depressive symptoms, including in severe cases with suicidal ideation. However, the potential for abuse and adverse effects justify the need for controlled use. Another obstacle to the use of ketamine is the price of the medication and the ideal conditions for its application, which makes it inaccessible to most patients. However, more studies need to be conducted to mitigate its adverse effects and clearly define its mechanism of action.